NaV1.9 Potentiates Oxidized Phospholipid-Induced TRP Responses Only under Inflammatory Conditions - Martin, Corinna; Stoffer, Carolin; Mohammadi, Milad; Hugo, Julian; Leipold, Enrico; Oehler, Beatrice; Rittner, Heike L.; Blum, Robert (Frontiers in Molecular Neuroscience, 2018)
Oxidized phospholipids (OxPL) like oxidized 1-palmitoyl-2-arachidonoyl-sn-glycero-3-phosphocholine (OxPAPC) were recently identified as novel proalgesic targets in acute and chronic inflammatory pain. These endogenous chemical irritants are generated in inflamed tissue and mediate their pain-inducing function by activating the transient receptor potential channels TRPA1 and TRPV1 expressed in sensory neurons. Notably, prototypical therapeutics interfering with OxPL were shown to inhibit TRP channel activation and pain behavior. Here, we asked how OxPL excite primary sensory neurons of dorsal root ganglia (DRG neurons from mice of either sex). Acute stimulation of sensory neurons with the prototypical OxPL 1-palmitoyl-2-glutaryl-sn-glycero-3-phosphocholine (PGPC) evoked repetitive calcium spikes in small-diameter neurons. As NaV1.9, a voltage-gated sodium channel involved in nociceptor excitability, was previously shown to be essential for the generation of calcium spikes in motoneurons, we asked if this channel is also important for OxPL mediated calcium spike and action potential generation in nociceptors. In wild-type and NaV1.9-deficient neurons, the action potential firing rate and the calcium spike frequency to an acute PGPC stimulus was similar. When preincubated with inflammatory mediators, both, the action potential firing rate and the calcium spike frequency were markedly increased in response to an acute PGPC stimulus. However, this potentiating effect was completely lost in NaV1.9-deficient small-diameter neurons. After treatment with inflammatory mediators, the resting membrane potential of NaV1.9 KO neurons was slightly more negative than that of wild-type control neurons. This suggests that NaV1.9 channels are active under this condition and therefore increases the ease with which action potentials are elicited after OxPL stimulation. In summary, our data suggest that NaV1.9 has a switch function to potentiate the receptor potentials induced by OxPL under inflammatory conditions. Since human NaV1.9 has been shown to mediate painful and painless channelopathies, this study provides new insights into the mechanism by which NaV1.9 amplifies stimuli of endogenous irritants under inflammatory conditions.